KOMUNIKASI MULTIKULTURAL PADA PRAKTIK PEMILIHAN UMUM (Studi Kasus Sosialisasi Komisi Pemilihan Umum Kabupaten Tangerang Tahun 2024) - Nurawaliah Ramadhani; Alamsyah; Suci Emelsi Jeffri (Social Science Academic, 2026)
This study aims to analyze the forms of multicultural communication implemented by the General Election Commission (KPU) of Tangerang Regency in the 2024 General Election socialization, identify community responses to its effectiveness, and map the obstacles encountered in a region with high ethnic and cultural diversity. Using a qualitative approach with a case study method, this research examines how adaptive communication strategies are employed to reach a heterogeneous society amidst challenges such as political literacy and potential polarization. The findings reveal that KPU implemented communication patterns capable of bridging differences in voters' cultural backgrounds through convergence strategies such as local language adjustments, interpersonal approaches, and segmenting communication media to increase public participation and maintain social stability during the democratic process, while utilizing divergence selectively for administrative clarity. Practically, this study serves as an evaluation for election organizers in designing more inclusive socialization models based on local wisdom in the future.